(untitled) (Research, Society and Development, 2021)
Detailed knowledge of chemical, petrographic and mineralogical compositions as well as the effects of applying rock powder on soil chemical properties and plant production are required for classifying these materials as soil remineralizers (SR), as according to Brazilian legislation in force. This study aimed to evaluate the potential of rock powders siltstone, tephrite and olivine melilitite, pure or mixed, on improving the fertility of a Cambisol and a Nitisol as well as the yield of soybean and barley crops grown in succession inside a greenhouse. For that purpose, these products were characterized as their granulometry, chemical, mineralogical and petrographic compositions. Based on the results, it was verified which products met the requirements for registration as SR established by the Normative Instruction Number 5 (NI5) from MAPA. Elemental chemical and grain size analyses indicated that all tested products met the NI5 requirements for their registration as SR. The mineral composition identified through petrographic analyses was confirmed by analyses performed via X-ray diffractometry techniques. Olivine melilitite rock, pure or mixed with siltstone, had the highest agronomic potential when compared to other powders, thus acknowledged as a SR. Although tephrite had little agronomic response on evaluated soils and crops, it also meets the SR requirements. Siltstone fulfilled most of NI5 criteria, except for exceeding the maximum content of free silica (quartz); therefore, it likely does not meet the requirements for its admittance as a SR.